Beyond art fundamentals a guide to emotion, mood, and storytelling for artists - Lewis, Marisa (3dtotalPublishing, 2016)
"Building on the foundations set by the popular Art Fundamentals book, Beyond Art Fundamentals shows artists how to take their work a step beyond techniques and mechanics. A memorable, unique image requires more than just accurate anatomy and choosing the right tools, after all! This impressive volume offers in-depth guidance on conveying mood and emotion and improving your images' storytelling through composition, character details, and atmosphere. Beyond Art Fundamentals is an ideal book both for hobbyists and new artists wanting to add extra depth to their work, as well as for skilled illustrators looking for a spark of new inspiration." -- Provided by publisher